Sistem Monitoring Real Time Pada Solar Panel Park - Ali Basrah Pulungan; Mujiati Delfitra (Universitas Negeri Padang, 2022)
The use of solar panels has begun to be used by the wider community to meet their electricity needs, but most of the installations are still static so that the performance of solar panels is low and monitoring tools are still manual. Monitoring that is done manually causes a waste of time and the limited amount of data generated. monitoring system helps solar panel users in monitoring the performance of solar panels. The development of the internet of things is to connect all equipment with the internet so that it can be monitored by users in real time. Users can obtain data information online. This research develops the use of the Arduino Uno controller and nodeMCU as a microcontroller and uses 4 current sensors and 4 voltage sensors in a solar panel park so that more data is generated. This process will be translated and set through Arduino Uno which functions as a data store and nodeMCU will request data and send it to thinger.io as an internet of thing device in graphical form. The data obtained can be monitored through the website page. This monitoring can make it easier to monitor the performance of solar panels in real time.